High-sensitivity C-reactive protein and interleukin-6 as risk predictors in patients with stable angina pectoris - Kunal, Shekhar; Meena, Pradeep Kumar; Pathak, Pooja; Mahla, Himanshu; Gupta, Kashish; Pathak, Vijay (International Journal of Advances in Medicine, 2020)
Background: Cardiovascular diseases are a leading cause of morbidity and mortality especially in developing countries such as India. Biomarkers such as high-sensitivity C-reactive protein (Hs-CRP) and interleukin-6 (IL-6) can help in risk stratification and better management of patients with stable angina. Methods: This was a prospective observational study wherein symptomatic patients with stable angina were enrolled. Coronary angiogram was done in those consenting to the procedure. Severity of coronary stenosis was graded as per the modified Gensini score (mGS). Hs-CRP and IL-6 levels were determined pre-procedure and 24 hours post percutaneous coronary intervention (PCI). Based on angiographic profile, patients were subdivided into four groups: group 1: normal coronaries, group 2: single vessel disease, group 3: double vessel disease and group 4: triple vessel disease. Primary outcome was occurrence of major adverse cardiovascular events over one-year period. Results: A total of 158 patients completed the study with a mean age of 62.8±9.6 years. A significant difference was observed between the four groups in terms of age, Hs-CRP and IL-6 levels. Of the 124 patients undergoing PCI, significant difference was observed in terms of pre and post procedure Hs-CRP (P<0.0001) and IL-6 levels (P<0.0001). Strong positive correlation was seen between Hs-CRP and IL-6 levels with modified Gensini scoring (mGS). Patients with MACE (15/158; 9.4%) had significantly higher levels of Hs-CRP and IL-6. Multivariate logistic regression analysis revealed that Hs-CRP, IL-6, ΔHs-CRP and ΔIL-6 were independent predictors of major adverse cardiovascular events (MACE). Conclusions: Hs-CRP and IL-6 levels were independent predictors of outcomes and can be used for risk stratification in these patients. .